ENTERPRISE RESOURCE PLANNING: SYSTEMATIC LITERATURE REVIEW - Febriana Roosmawati; Sambas Ade Kesuma; Iskandar Muda Damanik (CV. RADJA PUBLIKA, 2025)
Research on Enterprise Resource Planning is very interesting to do with the development of technology globally. Through a systematic literature review, an analysis is carried out related to the year of research , countries, topics discussed, theories used, and research methods. Thirty-five papers from the Science Direct, Pro Quest, Springer Link, and Emerald Insight databases were used for analysis. The analysis steps used the PRISMA method. From the analysis, it was found that ERP research has been increasing in recent years. The most widely discussed themes are the key to successful ERP implementation and the role of ERP in improving organizational performance. Finally, this study has limitations and suggests areas for future research.